Chemically deposited p-type MoBiCuS4 thin film for photoelectrochemical cell applications. (4th March 2022) - Henry, J.; Daniel, T.; Balasubramanian, V.; Mohanraj, K.; Sivakumar, G.
Abstract: MoBiCuS4 thin film has been deposited by chemical bath deposition and its structural, morphological, optical and photovoltaic properties have been studied. The XRD shows the presence of mixed phases (monoclinic and orthorhombic) and the crystallite size is found to be about 112 nm. The SEM images picturized the smaller sized irregular and bigger sized rectangular particles, the EDS analysis shows near stoichiometric ratio for the MoBiCuS4 thin film. MoBiCuS4 thin film exbihits higher optical absorption in the visible region and the bandgap is found to be 2 eV. p-type conductivity is noticed in the prepared film. The Photovoltaic (PV) performances of the MoBiCuS4 thin film demonstrates 1.2% photoconversion efficiency with Voc = 0.515 V and Jsc = 3 mA/cm 3 . This study suggests that the MoBiCuS4 thin film can be used as a absorber material for PV cells. GRAPHICAL ABSTRACT: UF0001